Masculinity as an Educational Process in the Reproduction of Gender Roles - ZM, Hamidsyukrie; Sumitro, Sumitro; Nursaptini, Nursaptini; Malik, Imam; Aryati, Risma Ade; Dewi, Baiq Yulia Rahma (Journal La Edusci, 2025)
This paper questions the symbolic production and educational reproduction of masculinity among the Sade community of Lombok, Indonesia. Based on ethnographic evidence, it critically analyzes the ways in which the traditional male authority is not only maintained through cultural practices and kinship systems but is actually taught, moralized and reproduced through generations. Although emergent forms of transitional masculinity, including male participation in household chores and shared household decision-making, may seem to be progressive, the results demonstrate that such changes frequently act to re-legitimize, rather than challenge, patriarchal authority. In this setting, masculinity is not so much a role as a symbolic regime, coded in ritual speech, spatial hierarchies, rights of inheritance, and public moral acknowledgment. The study will help in making critical contributions to the sociology of education by conceptualizing masculinity as a culturally constituted symbolic regime of governance and gendered pedagogy. It claims that learning in traditional societies is much more than schooling, and that it is carried out in ritualized speech, intergenerational imitation, and spatial-cultural coding. This gendered pedagogy socializes boys into power and speech and girls into service and silence and defines what is possible, permissible and desirable to both. The research criticizes equity-based educational interventions that focus on access or participation without focusing on the symbolic narratives of legitimacy and leadership. The results demand a radical reconsideration of gender-responsive education: an education that deconstructs the cultural logics of masculinity, de-centers patriarchal symbolism, and re-builds the moral architectures in which authority is learned and reproduced.